ASSOCIATION OF COLLABORATIVE CARE MODEL AND QUALITY OF LIFE IN SCHIZOPHRENIA - Dewa Ayu putu Ratna Juwita; Cokorda Bagus Jaya Lesmana; I Made Ady Wirawan (JURNAL WIDYA MEDIKA, 2023)
There has been emphasis on de-institutionalization of psychiatric care with a focus on collaborative care model (CCM) as a bedrock improving quality of life. This study measures the association of CCM and quality of life in schizophrenia. Schizophrenia receiving CCM and usual care (UC), each group was 41 and chosen by systematic random sampling follow this cohort retrospective study in Denpasar and Badung, Bali Province on April-November 2020. The outcomes are QoL (assessed by WHOQOL-BREF), socio-demographic, clinical characteristic, family support using Friedman questionnaire, stressor using PSS, coping using BRIEF-COPE, and medical adherence using MARS. Data was analyzed using alpha 5%. The mean age was 40.43 years. Except for marital status (p=